2022
DOI: 10.1111/epi.17380
|View full text |Cite
|
Sign up to set email alerts
|

Elevated photic response is followed by a rapid decay and depressed state in ictogenic networks

Abstract: Objective:The switch between nonseizure and seizure states involves profound alterations in network excitability and synchrony. In this study, we aimed to identify and compare features of neural excitability and dynamics across multiple zebrafish seizure and epilepsy models.Methods: Inspired by video-electroencephalographic recordings in patients, we developed a framework to study spontaneous and photically evoked neural and locomotor activity in zebrafish larvae, by combining high-throughput behavioral tracki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…To identify the impact of cilia loss on neuronal activity, we performed volumetric two-photon calcium imaging in 4 dpf elipsa larvae expressing the nuclear calcium indicator H2B-GCaMP6s in all differentiated neurons (figure 5A1) (Vladimirov et al, 2014). We performed 40 minute-long recordings consisting of spontaneous activity, followed by a series of photic stimulations that measure visual responses and can trigger seizure-like activity (Myren-Svelstad et al, 2022). We recorded 8 planes, used five light flashes of one minute each and collected data from four specific brain areas: the telencephalon, optic tectum/ thalamus, habenula, and hindbrain (figure 5A2) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the impact of cilia loss on neuronal activity, we performed volumetric two-photon calcium imaging in 4 dpf elipsa larvae expressing the nuclear calcium indicator H2B-GCaMP6s in all differentiated neurons (figure 5A1) (Vladimirov et al, 2014). We performed 40 minute-long recordings consisting of spontaneous activity, followed by a series of photic stimulations that measure visual responses and can trigger seizure-like activity (Myren-Svelstad et al, 2022). We recorded 8 planes, used five light flashes of one minute each and collected data from four specific brain areas: the telencephalon, optic tectum/ thalamus, habenula, and hindbrain (figure 5A2) .…”
Section: Resultsmentioning
confidence: 99%
“…We previously identified that photic stimulation serves as a good strategy to detect hyperexcitability and trigger seizures in epilepsy models (Myren-Svelstad et al, 2022). We did not observed any epileptic seizures in the 11 mutant animals analyzed, suggesting that ciliary loss does not lead to the occurrence of seizure in the elipsa mutants at 4 dpf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAAT2 is expressed in astroglia in the central nervous system (CNS) and regulates synaptic transmission by removing the extracellular glutamate ( Danbolt, 2001 ). Therefore, the hyperexcitability promoted by eaat2a -deficiency allows investigating seizure initiation and propagation in response to light stimulation ( Hotz et al, 2022 ; Myren-Svelstad et al, 2022 ). To this end, brain-wide increased neuronal excitability in eaat2a –/– zebrafish ( Danio rerio ) has been demonstrated via neuronal responses to transient light flashes ( Hotz et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the model of glutamate transporter EAAT2a-deficiency in the zebrafish offers a new platform for assessing chronic epilepsy ( Hotz et al, 2022 ). The lowered threshold for spontaneous epileptic seizures in the eaat2a mutant zebrafish model of perturbed glutamate clearance also facilitates triggering seizures by sensory light stimulation ( Yaksi et al, 2021 ; Myren-Svelstad et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%